« The Gallant boys at the front ». Portraits de soldats australiens, anglais et écossais retrouvés dans quatre carnets de dessins inédits du sculpteur Corneille Theunissen et de son fils André Theunissen - Catherine Limousin (In Situ)
“The Gallant Boys at the Front”, portraits of Australian, English and Scottish soldiers found in four unpublished sketchbooks by the sculptor Corneille Theunissen and his son André Theunissen. As a tribute to the 330 000 Australians soldiers, and English and Scottish soldiers who came to fight in France during the First World War, this article is an annotated edition of the most remarkable sketches found in four sketchbooks dealing with the Second Australian General Hospital at Wimereux in the Pas-de-Calais department, during the month of August 1916. Three of these sketchbooks are by the sculptor Corneille Theunissen (1863-1918) whilst the fourth is by his son André (1895-1936). This Australian field hospital was transferred from Egypt after the battle of the Dardanelles at the end of June 1916, and was able to take care of several hundred of the soldiers wounded at the battle of the Somme. Several of the soldiers and doctors depicted have been identified and the history of the hospital is recounted.